2022
DOI: 10.1002/aps3.11494
|View full text |Cite
|
Sign up to set email alerts
|

Asymbiotic in vitro seed germination, in vitro seedling development, and ex vitro acclimatization of Spiranthes

Abstract: Premise Reproducible seed propagation and production protocols were developed for Spiranthes and related taxa to facilitate ex situ conservation practices. Methods and Results Spiranthes seeds were scarified for 3‐ and 10‐min intervals in 10% sodium hypochlorite solution, then cultured on three seed germination media. After germination, seedlings were given one of the three photoperiod treatments, and then planted in one of four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…This review corroborates other studies in demonstrating that while many conditions can support asymbiotic germination of orchid seeds, species vary in the conditions that maximize their germination and protocorm development (Dixon, 1994 ; Kauth et al, 2008 ; Rasmussen et al, 2015 ; Teixeira da Silva et al, 2015 ; Zeng et al, 2016 ; Herrera et al, 2019 ; Zale et al, 2022a , b ). In addition to variation among species, there is also potential for variation at the intraspecific level due to population responses to environmental heterogeneity (Rasmussen et al, 2015 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This review corroborates other studies in demonstrating that while many conditions can support asymbiotic germination of orchid seeds, species vary in the conditions that maximize their germination and protocorm development (Dixon, 1994 ; Kauth et al, 2008 ; Rasmussen et al, 2015 ; Teixeira da Silva et al, 2015 ; Zeng et al, 2016 ; Herrera et al, 2019 ; Zale et al, 2022a , b ). In addition to variation among species, there is also potential for variation at the intraspecific level due to population responses to environmental heterogeneity (Rasmussen et al, 2015 ).…”
Section: Discussionsupporting
confidence: 85%
“…When using stronger hypochlorite solutions (e.g., >5%), the exposure time should be reduced to minimize damage to the embryo. For example, Zale et al ( 2022a ) found that seeds of Spiranthes Rich. lost germination ability with a 10‐min exposure to 10% NaOCl solution made from commercial bleach.…”
Section: Discussionmentioning
confidence: 99%
“…This was done by funding smaller projects dealing with 1–4 species each, as well as a larger project focused on 14 species. Participants in the smaller projects were allowed to work on a project of their choosing, and thus the projects differed widely in the types of protocols studied and the methods used (Seglias, 2022 ; Zale et al, 2022 ). This situation reflects the variety of exceptional species requiring attention, the variety of challenges they pose, and the differences in laboratory approaches and expertise, although it also presents a challenge in comparing projects.…”
Section: Discussionmentioning
confidence: 99%
“…The three projects focused on orchids (excluding the project used to leverage further funds) ranked lower in cost, ranging from $1579 to less than $3600 per point (the latter project on orchids also included a non‐orchid and the costs were not separated). These projects involved testing the effects of media on in vitro germination (Zale et al, 2022 ), as well as some testing of the seeds for tolerance to cryopreservation and banking, and these types of projects benefited from both the large volume of literature available on orchid seed germination in vitro and the large number of seeds available for experimental treatments (Kauth et al, 2008 ; Jolman et al, 2022 ). In addition, one garden working with orchid seeds noted that, although much of the cryopreservation work was dependent on full‐time skilled labor, some components, such as curation, viability testing, and data collection, could be done by trained volunteers and students, which helped to offset costs and scale up the work.…”
Section: Discussionmentioning
confidence: 99%
“…This work can give researchers a jumping‐off point for the development of in vitro germination protocols for new species in ex situ collections. In addition, Zale et al ( 2022 ) investigate seed germination requirements of the widespread Spiranthes Rich. genus and develop reproducible in vitro methods for the propagation of the species.…”
Section: Establishing Growing and Recovering Plants From In Vitro Cul...mentioning
confidence: 99%